Necessary and sufficient conditions of optimality for an optimal control problem with non-local boundary conditions and quadratic functional. - Criado-Adeanueva, Francisco; Criado-Torralba, Francisco; Odishelidze, Nana; Sánchez-Sáez, José-María (Wiley, 2013)
En este artículo se aborda el problema de control óptimo con un funcional cuadrático para la ecuación de Helmholtz con condiciones de frontera no locales. Se obtienen las condiciones necesarias y suficientes de optimalidad, sobre cuya base se demuestra la existencia y unicidad de la solución al problema óptimo.//In this paper the optimal control problem with a quadratic functional for Helmholtz equation with non-local boundary conditions is considered. Necessary and sufficient conditions of optimality are obtained on the basis of which the existence and uniqueness of a solution to the optimal problem is proved.
https://openpolicyfinder.jisc.ac.uk/id/publication/7540
Keywords: Helmholtz equation; Boundary values problems; Optimality for control problems